Temporal trends and regional variations in gastrointestinal cancer mortality in Peru, 2005-2014 - Hernández-Vásquez, A. (2016)
Objective: To estimate and analyze the evolution of mortality rates of gastrointestinal (GI) cancer in Peru and its regions between 2005-2014. Material and methods: We performed a nationwide secondary analysis of Peru’s Health Ministry registry of deaths during the period 2005-2014, with a focus on regional differences. Deaths registered with codes C15 to C25 (malignant neoplasms of digestive organs) from the ICD-10 were included. Calculation of age-standarized mortality rates and years of life lost (YLL) due to GI cancer per 100,000 habitants were also performed. Results: Data of 67,527 deaths from GI cancers was analyzed, 35,055 (51.91%) were women. In 2005, the number of GI cancer deaths was 6,484, for 2014, 7,532 cases were recorded. The GI cancer age-standarized mortality rates at the country level showed a decrease of 12.70% between 2005-2014. Stomach cancer presented the highest age-standarized mortality rate despite showing a downward trend in the last years, equal for gallbladder, liver and biliary tract, and esophagus cancer. Colorectal, small intestine and anus cancer show a progressive increase. In 2014, Callao (48.8), Huancavelica (48.5), La Libertad (39.6), Lambayeque (40.5) and Huanuco (38.9) had the highest rates. The three types of GI cancers with the highest rates of YLL in 2014 were stomach cancer (118.51), followed by liver and biliary tract cancer (58.68) and colorectal (44.86). Conclusion: GI cancer mortality in Peru is high and a priority issue in regions like Huancavelica, Huanuco, Callao, La Libertad and Lambayeque. Stomach cancer remains the most frequent GI cancer, but with a downward trend in the study period.